2003
DOI: 10.1542/peds.112.5.e389
|View full text |Cite
|
Sign up to set email alerts
|

Indoor and Outdoor Environmental Exposures, Parental Atopy, and Physician-Diagnosed Asthma in Taiwanese Schoolchildren

Abstract: ABSTRACT. Objective. Parental atopy and environmental exposures are recognized risk factors for childhood asthma. However, the relative contributions of specific risk factors and the overall contributions of indoor and outdoor exposures remain unexplored. This study was undertaken to identify risk factors, estimate the population attributable risk of each exposure, and compare the data for boys versus girls for physician-diagnosed asthma in Taiwanese schoolchildren.Methods. During a February to June 2001 cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 38 publications
3
63
0
Order By: Relevance
“…Similar trends have recently been reported in the Asia-Pacific areas [5,6,7] and Arabian Gulf countries [1,2,3,4,6,8]. Asthma is one of the most common chronic diseases in Saudi Arabia, affecting more than 2 million people [9].…”
Section: Introductionsupporting
confidence: 72%
“…Similar trends have recently been reported in the Asia-Pacific areas [5,6,7] and Arabian Gulf countries [1,2,3,4,6,8]. Asthma is one of the most common chronic diseases in Saudi Arabia, affecting more than 2 million people [9].…”
Section: Introductionsupporting
confidence: 72%
“…Age, sex, active smoking habits, parental atopic history, parental education, maternal smoking in pregnancy and ETS exposure at home have been reported to contribute to asthma and wheeze in childhood 6 22 25. We minimised interference from these confounders by recruiting lifelong non-smokers of similar age at study entry, and adjusting potential confounders by regression models.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that girls are more susceptible to selected non-allergen effects in their airways, and are thus possibly more susceptible to reactive airway disease when infected with Cpn. [23][24][25] Another explanation could be that some individuals, most often girls, might have an impaired ability to eliminate Cpn when infected. 26 If persistently infected over an extended period of time, the immune system might respond with higher levels of antibodies to Cpn which may not be protective.…”
Section: Discussionmentioning
confidence: 99%